PENGARUH PEMAHAMAN AGAMA ISLAM TERHADAP ETIKA BERPAKAIAN - Rita Oktaviani; Retno Triwoelandari; Ikhwan Hamdani (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2019)
AbstractThis study aims to find out 1) To find out the understanding of Islam towards the ethics of dressing class XI students in MAN 1 Bogor Regency 2) To find out the ethics of dressing class XI students in MAN 1 Bogor Regency 3) To find out the effect of understanding the religion of Islam on the ethics of dressing class girls XI at MAN 1 Bogor Regency. The method used is quantitative. Data collection techniques with a questionnaire and sample 60 students. The data that has been obtained is then analyzed by analyzing the validity, reliability, normality and homogeneity tests after calculating the Product Moment correlation formula. The results of this study indicate that: from the hypothesis test related to the influence of understanding of Islam on dress ethics in class XI in MAN 1 Bogor District, shows that: according to calculations using the Product Moment formula the rxy value of 0.707 was obtained and consulted with the value of r table at a significant level of 5% of 0.254. Because rxy tabel r table is at a significant level of 5%, the results are significant. At index 0.70-0.90 which means there is a strong or high correlation between variable X and variable Y so that the null hypothesis (Ho) is rejected the hypothesis (Ha) is accepted. This means that there is a significant strong or high relationship between the understanding of Islam and the ethics of dressing in MAN 1, Bogor Regency. Keywords: Understanding Religion; Dressed Ethics. AbstrakPenelitian ini bertujuan untuk mengetahui 1) Untuk mengetahui pemahaman agama Islam terhadap etika berpakaian siswi kelas XI  di MAN 1 Kabupaten Bogor 2) Untuk mengetahui etika berpakaian siswi kelas XI di MAN 1 Kabupaten Bogor 3) Untuk mengetahui pengaruh pemahaman agama Islam terhadap etika berpakaian siswi kelas XI di MAN 1 Kabupaten Bogor. Metode yang digunakan adalah kuantitatif. Teknik pengumpulan data dengan angket dan sempel siswi sebanyak 60 orang. Data yang telah diperoleh lalu dianalisis dengan analisis uji validitas, reliabilitas, normalitas dan homogenitas setelah menghitung dengan rumus korelasi Product Moment. Hasil penelitian ini menunjukan bahwa: dari uji hipotesis berkaitan dengan adanya pengaruh pemahaman agama Islam terhadap etika berpakaian pada kelas XI di MAN 1 Kabupaten Bogor. Menunjukan bahwa: sesuai perhitungan dengan menggunakan rumus Product Moment di peroleh nilai rxy sebesar 0.707 dan dikonsultasikan dengan nilai r tabel pada taraf signifikan 5% sebesar 0.254. Karena rxy ≥ r tabel  pada taraf signifikan 5% maka hasilnya signifikan. Pada indeks 0,70-0,90 yang berarti terdapat korelasi yang kuat atau tinggi antara variabel X dan variabel Y sehingga hipotesis nol (Ho) ditolak hipotesis (Ha) diterima. Hal ini berarti ada hubungan  kuat atau tinggi yang signifikan antara pemahaman agama Islam terhadap etika berpakaian di MAN 1 Kabupaten Bogor. Keywords: Pemahaman Agama; Etika Berpakaian.